The development and validation of a C-test and a pseudo-character test for online CFL assessment - Yang Xuan; Osborne Caitríona (Journal of China Computer-Assisted Language Learning)
Taking inspiration from a popular online English test, this study first documents the development of an achievement test containing a newly developed C-test and pseudo-character test for beginner-level Chinese learners. Then, based on the test results collected from 53 university learners and using statistical tools, analyses were conducted on its content validity, construct validity, criterion-related validity, difficulty, discrimination power, and reliability. Results indicate that this new achievement test has relatively satisfactory reliability and validity, with only minor issues that need to be addressed in future studies. Situated in the context of language assessment, the study sheds light on the application of the C-test and a pseudo-character section in both face-to-face and at-distance Chinese as a foreign language (CFL) classrooms. Furthermore, the study also provides practical and applicable methods for CFL teachers to develop their own assessments.